The potential neurological effect of the COVID‐19 vaccines: A review. (29th March 2021) - Lu, Lu; Xiong, Weixi; Mu, Jie; Zhang, Qi; Zhang, Hesheng; Zou, Ling; Li, Weimin; He, Li; Sander, Josemir W.; Zhou, Dong
Abstract: The coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has become a pandemic with people infected in almost all countries. The most efficient solution to end this pandemic is a safe and efficient vaccine. Classic platforms are used to develop vaccines including live‐attenuated vaccine, inactivated vaccine, protein subunit vaccine, and viral vector. Nucleic acid vaccine uses next‐generation platforms for their development. Vaccines are now rushing to the market. Eleven candidates are in advance development. These comprise inactivated vaccines, viral vector vaccine, nucleic acid vaccine, and the protein subunit vaccine platform, which are now quite advanced in trials in various geographic and ethnic populations. The reported severe adverse effects raised the worries about their safety. It becomes critical to know whether these vaccines will cause neurologic disorders like previously recognized vaccine‐related demyelinating diseases, fever‐induced seizure, and other possible deficits. We reviewed the most promising COVID‐2 vaccines with a particular interest in mechanism(s) and adverse effect(s). We exemplify potential neurological problems these vaccines could cause by looking at previous studies. The current evidence indicated a minor risk of the acute neurological disorders after the application. The observation of the long‐time effect is still needed.